Analisis Miskonsepsi Siswa Kelas XI IPA 1 SMA Negeri 1 Ma’rang Pada Materi Pokok Laju Reaksi - Fadhilah Fadhilah; Jusniar Jusniar; Muhammad Anwar (ChemEdu, 2020)
This descriptive research aims to analyze level and cause of student’s misconceptions on reaction rate topic. The subjects in research are 27 students of Grade XI IPA 1 students of SMAN 1 Ma'rang. The instruments are used in this experiment are essay test, observation sheet and semi-guided interviews. The data was analyzed by descriptive statistic method to obtain percentage of the misconception. The results showed that students’ misconception occurs in some of the sub concepts of reaction rate material. Percentages and categories of students’misconceptions on understanding the reaction rate, the factors that affect the rate of reaction , and the reaction order , are respectively 15 % is included in the low category , 18.7 % , including in the low category , and 15 % are included in the low category . Overall average student misconceptions on the material that is the reaction rate of 16.2 %. This shows that the misconception on the material reaction rate is low. The results also show that the misconception is caused by: 1) Students, the student preconceptions wrong, 2) Master, which does not provide an explanation in detail to the concept.